1994
DOI: 10.1017/s0950268800068400
|View full text |Cite
|
Sign up to set email alerts
|

Genome fingerprinting of Salmonella typhi by pulsed-field gel electrophoresis for subtyping common phage types

Abstract: The genomic DNA of 39 strains of Salmonella typhi isolated from local residents and patients who had visited countries in the Asian region was analysed for restriction fragment length polymorphisms (RFLP). Pulsed-field gel electrophoretic (PFGE) analysis of Xba I- and Spe I-generated genomic restriction fragments established 22 PFGE types whereas phage typing differentiated the 39 isolates into 9 distinct phage types. This study showed that PFGE is more discriminatory than phage typing as it is capable of subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…The PFGE technique of contour-clamped homogenous electric fields (CHEF) was used at the BBPE-Unit for the fingerprinting of 11 isolates, three from the north, four from the center, and four from the south, among the 81 ribotyped MDR isolates. XbaI endonuclease (Amersham Pharmacia Biotech, Uppsala, Sweden) was used for digestion of genomic DNA as described by Nair et al (25), and the DNA fragments were resolved with a CHEF-DRIII apparatus (Bio-Rad Laboratories, Richmond, Calif.) at 6 V/cm for 24 h at 14°C with a pulse time of 20 to 65 s and an electric field angle of 120°. Multimers of phage lambda and Low Range (New Englands Biolabs, Inc., Beverly, Mass), and Salmonella serovar Branderup digested by XbaI were used as molecular size standards.…”
Section: Bacterialmentioning
confidence: 99%
“…The PFGE technique of contour-clamped homogenous electric fields (CHEF) was used at the BBPE-Unit for the fingerprinting of 11 isolates, three from the north, four from the center, and four from the south, among the 81 ribotyped MDR isolates. XbaI endonuclease (Amersham Pharmacia Biotech, Uppsala, Sweden) was used for digestion of genomic DNA as described by Nair et al (25), and the DNA fragments were resolved with a CHEF-DRIII apparatus (Bio-Rad Laboratories, Richmond, Calif.) at 6 V/cm for 24 h at 14°C with a pulse time of 20 to 65 s and an electric field angle of 120°. Multimers of phage lambda and Low Range (New Englands Biolabs, Inc., Beverly, Mass), and Salmonella serovar Branderup digested by XbaI were used as molecular size standards.…”
Section: Bacterialmentioning
confidence: 99%
“…A more comprehensive PFGE analysis of 120 S. enterica serovar Typhi isolates from Southeast Asia (60 from Malaysia, 50 from Indonesia, and 10 from Thailand) also found considerable genetic diversity among them, although some PFGE profiles were shared between countries (38). Nair et al (23) reported that many PFGE types are circulating in Asia. Our findings are therefore in concordance with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was not to replace the classical typing methods for Salmonella serovars, such as serotyping and phage typing, but rather to complement these methods with a rapid, simple, and sensitive molecular technique such as PCR-SSCP. There is no doubt that established typing methods such as PFGE and ribotyping could be used in the differentiation of Salmonella serovars, although it may come as a surprise that PFGE has primarily been used only for intraserovar molecular characterization of salmonellae (18,20,32). Ribotyping, on the other hand, has been carried out to characterize Salmonella serotypes Reading, Senftenberg, and Typhimurium (3).…”
Section: Discussionmentioning
confidence: 99%
“…These DNA-related techniques include ribotyping (3), pulsedfield gel electrophoresis (PFGE) (18,20,32), IS200 fingerprinting (4), PCR-ribotyping (12), ribosomal DNA intergenic spacer amplification and heteroduplex analysis (9), amplified fragment length polymorphism (1, 21), automated 5Ј nuclease PCR assay (7), and random amplified polymorphic DNA analysis (30).…”
mentioning
confidence: 99%